Tinjauan Teknologi Cerdas Pendukung Pemulihan Ekonomi UMKM Terdampak Covid-19 - Dian Margahayu (APIC, 2021)
The implementation of Large-Scale Social Restrictions (PSBB) in various provinces in Indonesia has an impact on the Indonesian economy. The publication of the Analysis of the Covid-19 Impact Survey Results by BPS stated that 82.29% UMB and 84.20% MSE experienced a decrease in income. The government through the Covid-19 Handling Committee and National Economic Recovery launched the National Economic Recovery program, one of which was to provide a stimulus for business capital assistance to MSMEs. Apart from stimulus assistance, technology is also needed to accelerate economic recovery. Smart technologies that can be tried to be applied in the recovery of the national economy, including blockchain, smart contracts, e-commerce, IoT and cloud computing.